An adaptive digital image watermarking scheme with PSO, DWT and XFCM - Mitashe, Mashruha Raquib; Habib, Ahnaf Rafid Bin; Razzaque, Anindita; Tanima, Ismat Ara; Uddin, Jia (© 2017 IEEE, 2018)
This article was published in the IEEE Xplore [© 2017 IEEE] and the definite version is available at : http://doi.org/10.1109/ICIVPR.2017.7890868 The Journal's website is at: http://ieeexplore.ieee.org/document/7890868/?reload=true